The Development Model of Store Atmosphere in Culinary Business to Increase the Purchasing Interest of Society in the Sub-District of Percut Sei Tuan - Nel Arianty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Culinary business has a lot of competition which is faced by business actors. So, in the culinary business, it demands every effort to be able to compete and to defend against competitors.